The Least Glory: The Great War as Seen by Women Poets - Bean, Joann (My University, 1982)
This essay explores a neglected aspect of Great War literature, the verse written by women. The essay suggests possible reasons for the long neglect of the poetry written by women and points to the work yet to be done in the area,in addition to making some initial critical comment on the poetry. Before discussing the poems which women wrote about the Great War experience it was necessary to find them and for that reason this work is divided into two parts: the poems which form the appendix and, in an Introduction and two chapters, the first critical appraisal of this material.
The poems, which were found tn popular and literary journals, in collected works and anthologies, are gathered here and presented for consideration for the first time. The twenty-nine poems in the appendix were chosen from among thousands available, a quantity which clearly provided a wide range of quality. My first consideration in choosing the poems was to choose those in which the poet matched the content and the treatment of the content. discarded the clearly sentimental and the trite and looked for poetic attempts to come to terms with basic emotions and experiences. Some of the poems of lesser quality or poems with a few good effects or ideas have been included in the critical commentary. Other poems have been included in the body of the essay to illustrate themes or attitudes.
One of the problems for an anthologist is to decide on the categories for arranging poems. War anthologies are sometimes printed alphabetically by author and more often by placing poems with similar attitudes together. I decided to use the latter method. When the poems had been selected and arranged so that those which were similar in content were together it became clear that chronology is also important. As the war continues the poetry changes. The earliest poems, particularly those printed in the United States, express anger and seek causes for war. The later poems express despair and disillusionment. Thus the essay not only discusses common themes and symbols used by the poets to describe their experience of the Great War it also shows the development of attitudes to the war as expressed in poetry.
Keywords: Great War; Women Poets; poetry; literature; women